Prioritization of Factors Affecting Sustainability Property Improvement by Using Analytical Hierarchy Process and Important-Satisfaction Model: The Case of TAIPEI 101 Tower - Tse-Hsiung Lin; Shen-Guan Shih (Applied Sciences, 2020)
Almost without exceptions office buildings in the world investigate the approaches of optimizing the building operation and property facilities in order to maintain the best conditions of the building from the first day of opening. For sustainable buildings, how to make continuous profit must rely on the maintenance and improvement of facilities to satisfy users. However, building managers often have trouble prioritizing improvement projects toward their sustainable objectives due to the large number of facilities that have different durability years and the importance and satisfaction of these facilities to users are also different. In the past, financial consideration was usually the only one that matters when improvement of facilities was brought up. Users feedback of satisfaction was not taken into consideration, resulting in huge expenditures did not bring in high user satisfaction. This research, by scientific analysis of the data from user feedback, applies the Analytic Hierarchy Process (AHP) using TAIPEI 101 Tower as a case study to explore the key factors affecting tenants’ willingness to lease office buildings by distributing questionnaires to real estate experts. By filtering out key indicators related to property facilities that users care about, this study used Importance and Satisfaction Analysis (IS Analysis) to identify items that need urgent improvement. This innovative analysis methodology can systematically and logically find out the priority of improvement projects, assisting building managers effectively invest limited resources in projects with substantial benefit, which is helpful for sustainable property management.